2020
DOI: 10.1038/s41388-020-1203-x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell-intrinsic function of CD177 in attenuating β-catenin signaling

Abstract: Aiming to identify immune molecules with a novel function in cancer pathogenesis, we found the cluster of differentiation 177 ( CD177 ), a known neutrophil antigen, to be positively correlated with relapse-free (RFS), metastasis-free (MFS) or overall survival (OS) in breast cancer. Additionally, CD177 expression is correlated with good prognosis in several other solid cancers including prostate, cervical, and lung. Focusing on breast cancer, we found that CD177 is expressed in normal bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Beyond neutrophils, the presence of CD177 on epithelial cells, in cervical cancer, prostate cancer and ovarian cancer has been documented. Analysis of CD177 in mammary epithelial cells revealed a strong CD177 expression on epithelial cells that was significantly reduced in paired cancer specimens [73]. These data suggest CD177 molecule as a cancer cell-intrinsic tumor suppressor and introduced this molecule as a potential good prognostic factor in different cancer types [73].…”
Section: Nb Antigenmentioning
confidence: 87%
See 1 more Smart Citation
“…Beyond neutrophils, the presence of CD177 on epithelial cells, in cervical cancer, prostate cancer and ovarian cancer has been documented. Analysis of CD177 in mammary epithelial cells revealed a strong CD177 expression on epithelial cells that was significantly reduced in paired cancer specimens [73]. These data suggest CD177 molecule as a cancer cell-intrinsic tumor suppressor and introduced this molecule as a potential good prognostic factor in different cancer types [73].…”
Section: Nb Antigenmentioning
confidence: 87%
“…Analysis of CD177 in mammary epithelial cells revealed a strong CD177 expression on epithelial cells that was significantly reduced in paired cancer specimens [73]. These data suggest CD177 molecule as a cancer cell-intrinsic tumor suppressor and introduced this molecule as a potential good prognostic factor in different cancer types [73]. A recent study documented TRALI induction in a CD177 pre-immunized recipient after transfusion with packed red blood cells (PRBC) from CD177 positive donors, but not CD177 negative donors.…”
Section: Nb Antigenmentioning
confidence: 99%
“…In a recent publication, the high CD177 levels discriminated against non‐survivors patients with COVID‐19 [32]. Also, in ovarian cancer, CD177 expression on tumour tissue is related to tumour malignancy and a bad prognosis [33], while in breast and cervical cancers, it is related to shorter overall survival [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the specific mechanism of action of MMP3 and MMP1 in colorectal cancer needs to be further studied. CD177 is a glycosylphosphatidylinositol-linked cell surface protein that is heterogeneously expressed by neutrophils, and its expression is associated with good prognosis in breast, prostate, cervical, and lung cancers (47). Studies have shown that CD177 + neutrophils inhibit epithelial tumorigenesis and serve as independent predictors of prognosis in patients with CRC (48).…”
Section: Discussionmentioning
confidence: 99%